Filsafat Nir-Kekerasan Dalam Perspektif Mohandas Karamchand Gandhi Dan Relevansinya Dalam Pencegahan Gerakan Radikalisme Di Indonesia - Siswadi, Gede Agus (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Radicalism from a religious point of view refers to an extreme understanding and refers to fundamental religious fundamentalism with very high religious fanaticism. This understanding will be very easy to trigger acts of violence, conflict, and division because they see differences as a threat to the religious existence of these radicalism groups, and differences are also considered enemies that must be destroyed. With this, efforts are needed to minimize radicalism movements. This study focuses on the thoughts and teachings of Mahātma Gandhi regarding the most monumental ahimsa of his movement in India. By using the philosophical hermeneutic method, the result of this research is that the radicalism movement emerged as a result of the humanity and fading attitude of tolerance and religious fanaticism that was too high. Gandhi viewed that every religion essentially teaches love and non-violence. Humans can find love by practicing satyagraha which is always on the path of truth. By emphasizing the ahimsa aspect, humans will be able to find the truth. On the basis of this truth, the light of love will be revealed, and see that all human beings originate from the same source. On the basis of this love, humans are intertwined in one family and brotherhood.